INSTRUCTIONAL DESIGN OF GERLACK & ELY MODEL IN THE APPLICATION OF PANCASILA MORAL VALUES IN CLASS XI AT SMAN 1 SUKODADI - Rohyan, Muhammad Rois; Machsunah, Yayuk Chayatun (Journal on Research and Review of Educational Innovation, 2024)
Adolescence is the most turbulent period in humans, so there are many changes in children's behavior at this time; instilling good moral values in students is needed to live life both at school, at home, and in society. This article aims to provide a new perspective in developing learning strategies in schools to help improve and improve morals in students, using the Gerlack & Ely learning model in the hope of assisting students in understanding the moral values contained in Pancasila and being able to practice in everyday life. With this learning model, students will be invited to work together to solve problems in learning so that the learning atmosphere will not be boring. Generally, learning in schools often uses a one-way communication system, namely, the teacher explains, and students only listen; this will feel boring and lazy. Applying the Gerlack & Ely learning model can increase student activeness in the learning process so that the material taught can be more easily understood. It will later be practiced in everyday life.